REAKSI PASAR DI SEKITAR PERISTIWA KENAIKAN HARGA BBM PADA RETURN SAHAM IDX30 DI BURSA EFEK INDONESIA - Saputra, I Ketut Gede; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of  this study is to determine the significance of average abnormal return around the fuel price increase evens as well as testing the significance of differences in average abnormal return before and after the events of fuel price increase. Secondary data isuused on this study. Determination of the sample is done through by census method. Testing  of abnormal return around the fuel price inrease use statistical test by one sample t-test and paired sample t-test to testing the diffrences of abnormal return before and after the event of fuel price increase. The results of this research show that by testing the first hypothesis that no market reaction around fuel price increase shown where there is no significant positive abnormal return. The test on second hypothesis that the announcement of fuel price increases event do not affect investor’s reaction both before and after the announcement shown that no significant positive abnormal return value.
Keywords: Market Reaction, Event Study, Abnormal Return